Advances in the classification of round cell sarcomas. Issue 1 (27th December 2021) - Le Loarer, Francois; Baud, Jessica; Azmani, Rihab; Michot, Audrey; Karanian, Marie; Pissaloux, Daniel
Abstract : Round cell sarcomas represent a diagnostic challenge for pathologists, owing to the poorly differentiated features of these high‐grade tumours. The diagnosis of round cell sarcoma requires large immunohistochemical panels and molecular testing in many cases. This spectrum of malignancies is largely dominated by Ewing sarcomas (ESs), which represent the most common family of these tumours. Nonetheless, new families have been delineated in the past few years, with the addition of two additional families in the 2020 World Health Organization classification of bone and soft tissue tumours, namely sarcomas with CIC rearrangements and sarcomas with BCOR alterations. EWSR1, one of the genes involved in the driver fusion of ESs, is also implicated in the translocation of many other tumours with heterogeneous lineages and variable levels of aggressiveness. Round cell sarcomas associated with fusions inwhich EWSR1 is partnered with genes encoding transcription factors distinct from those of the 'Ewing family' represent a heterogeneous group of rare tumours that require further study to determine whether their fusions may or not define a specific subgroup. They include mainly sarcomas with NFATc2 rearrangements and sarcomas with PATZ1 rearrangements. At this point, PATZ1 fusions seem to be associated with tumours of high clinical and morphological heterogeneity. Molecular studies have also helped in the identification of more consistent biomarkers that give tremendous help to pathologists in triaging, if not diagnosing, these tumours in practice. This review compiles the latest accumulated evidence regarding round cell sarcomas, and discusses the areas that are still under investigation. Abstract : Undifferentiated round cell sarcomas are strongly linked to translocations that drive their pathogenesis. Ewing sarcomas represent by far the most common type of these tumours, but the advent of next‐generation sequencing techniques has paved the way for recognising and better delineating other distinct families that were previously only partially identified on morphological grounds. These newly identified groups include CIC ‐rearranged sarcomas, sarcomas with BCOR genetic alterations, and round cell sarcomas with EWSR1 ‐non‐ETS fusions.